Penilaian Kerugian Ekonomi Usaha Tani Padi Sawah dan Status Keberlanjutan Pengelolaan Saluran Irigasi Sekunder Vanderwijck di Yogyakarta - Miftahul Azis; Aceng Hidayat; Ahyar Ismail (Analisis Kebijakan Pertanian, 2020)
Sustainability is an essential aspect of agricultural development and multidimensional. One of the crucial elements in agricultural development is water supply. Distribution of irrigation water from upstream to downstream experienced various obstacles related to the existence of different interests and management. This research aimed to estimate economic losses of rice farming and analyze sustainability status of Vanderwijck secondary irrigation channels management in Yogyakarta. The economic losses of rice farming were income loss due to a change in environmental function that impacted human livelihood. The status of sustainable water resources use in irrigation channels was analyzed using the ordination technique through the Multidimensional Scaling (MDS) method. Results of this study concluded that in the Vanderwijck irrigation, the estimated potential loss of production in a farmer group who experienced water shortages (with 10.6-hectare acreage) was 106.2 tons per year or equal to the possible production losses of one growing season. This was also equal to the potential loss of farmers’ income by 200.7 million rupiahs per year. The sustainability status of Vanderwijck irrigation channel management based on MDS analysis was spread across the sustainable category for ecological and economic dimensions; and the entirely sustainable category for social, policies, and technical and financial supports. Because of irrigation channels management is at various levels of authority, to have better sustainability management, it is recommended to prioritize managing the key factors that have the lowest status from the five dimensions above. AbstrakKeberlanjutan merupakan aspek penting dalam pembangunan pertanian dan bersifat multidimensi. Salah satu aspek penting dalam pembangunan pertanian adalah ketersediaan air. Distribusi air irigasi dari hulu ke hilir mengalami berbagai hambatan terkait perbedaan kepentingan dan kewenangan pengelolaan. Penelitian ini bertujuan untuk mengestimasi kerugian ekonomi usaha tani padi dan menganalisis status keberlanjutan pengelolaan saluran Irigasi Sekunder Vanderwijck di Yogyakarta. Kerugian ekonomi usaha tani adalah pendapatan yang hilang karena perubahan fungsi lingkungan yang berdampak terhadap kehidupan manusia. Status keberlanjutan pemanfaatan sumber daya air pada saluran irigasi dianalisis menggunakan teknik ordinasi melalui metode Multidimensional Scalling (MDS). Hasil penelitian menyimpulkan bahwa di daerah Irigasi Vanderwijck, kelompok petani yang mengalami kekurangan air (dengan luas 10,6 hektare) diestimasi mempunyai potensi kerugian produksi sebesar 106,20 ton per tahun atau setara dengan produksi satu musim tanam. Nilai ini juga sama dengan potensi kehilangan penerimaan usaha tani sebesar Rp200,7 juta per tahun. Status keberlanjutan pengelolaan saluran Irigasi Vanderwijck berdasarkan analisis MDS tersebar pada kategori berkelanjutan untuk dimensi ekologi dan ekonomi; dan cukup berkelanjutan untuk dimensi sosial, kebijakan, dan dukungan teknis serta finansial. Karena pengelolaan saluran irigasi didasarkan di berbagai tingkat kewenangan, agar keberlanjutan pengelolaan menjadi lebih baik, disarankan untuk memprioritaskan mengelola faktor kunci dari kelima dimensi tersebut di atas yang mempunyai nilai status paling rendah.